Fenomena FOMO (Fear of Missing Out) pada Masyarakat Perkotaan di Indonesia - Nurhasanah, Anis (Mandalika: Jurnal Ilmu Pendidikan dan Bahasa, 2024)
The Fear of Missing Out (FoMO) phenomenon has become a significant issue in Indonesia's urban society, especially with the increasing internet penetration and social media use. FoMO is defined as fear or anxiety about missing an important moment, information, or experience. This study aims to analyze the causative factors, impacts, and mitigation strategies of FoMO in urban communities in Indonesia. The method used is a literature study, which involves analyzing data from various journals, articles, and academic publications during the 2018-2023 period. The results showed that intensive social media use, social pressure in urban environments, and low self-control were the main factors that triggered FoMO. The impact of FoMO includes increased stress, decreased productivity, disruption of social relationships, and consumptive behavior. However, strategies such as increasing digital literacy, managing social media usage time, and practicing mindfulness have proven effective in reducing the negative impact of FoMO.